Characterization of the SEHOUE – MASSI clay used for chemical purification: case of GBAGO ponds (Porto-Novo. Republic of Benin) - CAKPO, Romuald Arthur; TOMETIN, A. S. Lyde; FANOU, Narcisse; GOUDJO, Ferdinand; SAGBO, Etienne; SOUMANOU, Mohamed (My University, 2023)
The principal objective of this research is to develop the local fisheries with the aim of increasing the productivity of local halieutics resources. The depollution of the studied ponds was made with the clay of SEHOUE-MASSI which is a locality located at 98 km of the town of Cotonou. The site of SEHOUE-MASSI is located between 213'E and 216'E then between 657' and 659'N in LAMA depression with generally flat relief. Ten wells with the mesh of 100m and maximum depth 5m for the majority and sometimes 7m were explored. The clays obtained are plastic, of bank gray color in general. The samples are taken according to the colors observed according to depths and are put in sachets from 5 to 10kg. The clay reserve on the site of SEHOUE-MASSI is estimated at 15,30,000 tonnes according to work's of the Beninese Office of Geological and Mining Research (BOGMR). The purpose of the depollution of the studied ponds is to increase the productivity on a scale of the local fisheries by treating the ponds with lower cost than to booster local consumption and the marketing of the halieutics products in order to reduce the importation of the imported frozen products. The results obtained showed that clays used can cleanse the water samples of GBAGO ponds.
Keywords: Depollution; species halieutics; decontamination; ponds; clay.